New Proofs of Monotonicity of Period Function for Cubic Elliptic Hamiltonian (Journal of Nonlinear Modeling and Analysis, 2024)
In [1] S.-N. Chow and J. A. Sanders proved that the period function is monotone for elliptic Hamiltonian of degree 3. In this paper we significantly simplify their proof, and give a new way to prove this fact, which may be used in other problems.
Keywords: Periodic function; elliptic Hamiltonian; Abelian integrals.